Gestão dos recursos pesqueiros do complexo estuarinolagunar de Cananéia-Iguape-Ilha Comprida, litoral sul de São Paulo, Brasil - Mendonça, Jocemar Tomasino (2007)
Mendonça J. T., 2007 The south coast of the São Paulo State the fisheries resources are the economic base of the region, with a variety of fish, crustaceans and clams, with diversification of the arts fishiries by the local communities. The work was developed in the south coast of the State of São Paulo (Brazil), in the Estuarino-lagunar Iguape-Cananéia-Paranaguá Complex, in the area called of lagamar of Cananéia, Iguape and Ilha Comprida, and final portion in the Ribeira of Iguape river, with the total period of the information between February of 1995 the December of 2006, with dates of each city. The region fisheries activit presents a concern aspect, but don t despairing aspect, since involve three cities (Cananéia, Iguape and Ilha Comprida cities) with IDH medium and clear conditions of improvements. It involves 50 fishing communities with particular and similar characteristics between itself, with the agricultural comunities with lesser incomes, having devotion to fisheries and the parallels activities as agriculture and the extrativismo, mainly vegetal. The main fishing products of the south coast are: broadband anchovy (Anchoviella lepidentostole), the seabob shrimp (Xiphopenaeus kroyeri), the king weakfish (Macrodon ancylodon), the grey mullet (Mugil platanus), the white mullet (Mugil curema), the whitemouth croaker (Micropogonias furnieri), the blue swimming crab (Callinectes sapidus) and the mangrove oyster (Crassostrea brasiliana). The fishing fleet of the region has as characteristic to be of small scale and artesanal, with boats wooden with small autonomy of sea or of estuary, with high number of arts and methods of fisheries, as well as dependence of harvests. The problems main problems found in the activity fishing are the lack or inadequate fiscalization, the commercialization of the products the values insufficient for the maintenance of the activity the levels compensatory and deficiency in the management fisheries regional, without endorsement of the state and federal managing agencies. Seven species presented significant reduction in its abundance (seabob shrimp, broadband anchovy, mangrove oyster, white mullet, king weakfish, blue crab and atlantic thread herring Opistonema oglinum); three species presented increase in the abundance index (pink shrimp, crab-uçá and grey mullet); and four has its abundance indices stasble (whitemouth croaker, white sea catfish Genidens barbus, southern white shrimp Litopenaeus schmitti and castin leatherjacket Oligoplites saliens). To implement the fisheries recources management is necessary the strengthem of the Management Council of the APA-CIP with co-management, of deliberative character and with discussion of the problems and guiding of the solutions, including normatives, control and promotion of the activity through the institutions that compose it. The biggest problem for the implementation of a co-management is the lack of compromise of the management agencies with the society, presenting lack structure agencies, as well as the lack of will politics to share decisions and to divide the actions power. The fisheries management would have to be ecosystem approach fisheries, since the fishing of some species (multispecific), dependents of harvests, with fisheries diversify, arts and methods fisheries, with other productive activities to fishery. For fisheries resources with recuction of abundance indices the fisheries management could be local with the species that have its confined live cycles in the region, don t making part of the captures in other areas of the Brazilian coast, having as main management instrument the limitation of the fisheries effort through the fisheries cadastre and licensing of the fishermen and boats in regional way, with administration through the Management Council, its assign to rules and requirements to guarantee the activity to the fishermen local. For fisheries resources that have its live cycles outside region, to make part of the captures of other fishing capture to long of Brasilian coast, the best way of fisheries management, possibly would be of analysis of all area of fish of the resource, with joint actions with all involved ones, limiting the number of users, establishing exploration areas, with new licensing and permissions fisheries of the boats that will act in each area.